2016
DOI: 10.1007/s10943-016-0304-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Self-Classified Religious and Spiritual Groups of Emerging Adult Males: Conceptual and Psychometric Challenges

Abstract: This study sought to determine whether measures of religion and spirituality could discriminate between emerging adult males who self-identified as both religious and spiritual (B), religious only (R), spiritual only (S), or neither (N). Two religion measures and three spirituality measures were employed to assess the constructs. It was predicted that those who self-identify as religious only would score significantly higher on the religion measures than those who identified as spiritual only, and those that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Relatedly, it may be that university students do not integrate institutionalized religion and acceptance of others (item 14) and selfless caring (item 13), as these two items loaded most strongly onto Selflessness. University students may be prone to identify as "spiritual, but not religious," making the differentiation between religiosity and spirituality in this population difficult (Handal et al 2014;Handal et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, it may be that university students do not integrate institutionalized religion and acceptance of others (item 14) and selfless caring (item 13), as these two items loaded most strongly onto Selflessness. University students may be prone to identify as "spiritual, but not religious," making the differentiation between religiosity and spirituality in this population difficult (Handal et al 2014;Handal et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This method is often used to recruit hidden populations that are difficult for researchers to access (Faugier & Sargeant, 1997) -as it is the case of sceptics and atheists, considering that most of the Portuguese population professes a religious creed (Censos, 2011). In conducting the study, one concern was to ensure representativeness among practising believers, non-practising believers, sceptics and atheists in order to overcome the bias that a sample predominantly of believers might otherwise introduce to the results, as has already been demonstrated in other studies (e.g., Handal et al, 2017;Zinnbauer et al, 1997). To mitigate this effect, the study of Kimball et al (2009) was taken into account, which concluded that individuals from Humanities, in special social sciences, tend to be more secular or less religious, as compared to those from scientific areas.…”
Section: Methodsmentioning
confidence: 99%
“…In order to solve this, Handal et al (2017) conducted a study in which they sought to verify to what extent spirituality is conceptually independent of religiosity by comparing measures that assess both constructs. The authors concluded that these constructs actually converge and that the hypothesis of their conceptual independence is unsupported by the results.…”
mentioning
confidence: 99%
See 2 more Smart Citations